2021
DOI: 10.3389/fgene.2021.664379
|View full text |Cite|
|
Sign up to set email alerts
|

Putative Causal Variants Are Enriched in Annotated Functional Regions From Six Bovine Tissues

Abstract: Genetic variants which affect complex traits (causal variants) are thought to be found in functional regions of the genome. Identifying causal variants would be useful for predicting complex trait phenotypes in dairy cows, however, functional regions are poorly annotated in the bovine genome. Functional regions can be identified on a genome-wide scale by assaying for post-translational modifications to histone proteins (histone modifications) and proteins interacting with the genome (e.g., transcription factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…If ‫ܴܦܨ‬ ஐ >= 0.05 for an omics feature, no trans e/sQTL were selected. Also, those e/sQTL under at least two ChIP-seq peaks identified from multiple studies 6,42,43 were used in the Bayesian analysis described below.…”
Section: Methodsmentioning
confidence: 99%
“…If ‫ܴܦܨ‬ ஐ >= 0.05 for an omics feature, no trans e/sQTL were selected. Also, those e/sQTL under at least two ChIP-seq peaks identified from multiple studies 6,42,43 were used in the Bayesian analysis described below.…”
Section: Methodsmentioning
confidence: 99%
“…These results are in accordance with a previous study in bovine rumen tissue from our group, where the CTFC peaks identified for BW and AW represented approximately 0.6% of the cattle genome (bosTau8) [ 8 ]. Another study in cattle identified CTCF peaks in the liver, lung, mammary gland, kidney, heart, and spleen in lactating Holstein cows, totaling an average of 456,881 CTCF peaks for all samples and tissues (with a minimum number of ~60,000 peaks and a maximum number of 790,000 peaks per sample), representing ~7% of the cattle genome (bosTau8), showing a higher number of peaks compared to our study probably due to the higher number of samples and number of reads [ 34 ]. However, their samples presented a great variability in the number of CTCF peaks depending on the tissue and replicate [ 34 ].…”
Section: Discussionmentioning
confidence: 83%
“…Although large numbers of regulatory elements have been identified in cattle recently, many more regulatory non-coding elements are expected to be identified in additional tissues and conditions. A few studies have used CTCF ChIP-seq to identify functional regions in animals, such as mouse [ 29 , 30 , 31 ], sheep [ 32 , 33 ], and cattle [ 34 ]. A recent study in lactating dairy cows identified millions of functional regions in the cattle genome using ChIP-seq data from six tissues (heart, kidney, liver, lung, mammary, and spleen), including CTCF-binding sites and differential binding sites between tissues [ 18 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These pieces of evidence support that MTAO can be used to identify omics features, i.e., regulatory elements, of high importance to complex traits. Apart from gene expression and splicing, there are many other types of quantitative omics features such as the height of ChIP-seq peaks 38 and allele-specific imbalance 27 which can also be analysed by MTAO. Moreover, MTAO is summary-data based so it can be applied to any results from GSOR or conventional TWAS, as long as there are beta and standard error estimates for the association between the omics feature and the phenotype.…”
Section: Discussionmentioning
confidence: 99%